The legitimacy of Indonesian language in contract formation following Supreme Court Circular Letter Number 3 of 2023 - Inri Januar; Budi Santoso; Rachmi Sulistyarini; Siti Hamidah (Cita Konsultindo Research Center, 2024)
The purpose of this study is to examine whether Indonesian legislation permits using foreign languages in contract drafting. It employs normative research methods with primary and secondary legal materials. The findings reveal a vertical normative conflict between lower and higher regulations, leading to differences in interpretation and creating legal uncertainty for parties in agreements. Using the Indonesian language in contracts is essential because it acts as one of the national symbols, compelling the state to mandate its use in agreements involving Indonesian citizens. However, in contracts, this requirement can be bypassed through the choice of law principle. In addition, the study addresses the